2005
DOI: 10.1128/aem.71.12.8565-8572.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aeration Cycles on Nitrifying Bacterial Populations and Nitrogen Removal in Intermittently Aerated Reactors

Abstract: The effects of the lengths of aeration and nonaeration periods on nitrogen removal and the nitrifying bacterial community structure were assessed in intermittently aerated (IA) reactors treating digested swine wastewater. Five IA reactors were operated in parallel with different aeration-to-nonaeration time ratios (ANA). Populations of ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB) were monitored using 16S rRNA slot blot hybridizations. AOB species diversity was assessed using amoA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 45 publications
3
49
2
Order By: Relevance
“…Previous studies indicated that Chloroflexia was suited to live under brackish, nutrient-rich conditions [78]. Nitrospira, which was found to be more abundant at sites far away from the pollution source (D2, D3, J2, and J3), has often been found in freshwater ecosystems [79,80], sewage treatment systems [81], and anoxic environments as nitrite oxidizers [82]. Based on the results of RDA (Figure 9a), Nitrospira was positively correlated with NH 4 + -N, NO 3 Cl − -N, TOC, and TSI, but negatively correlated with RI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that Chloroflexia was suited to live under brackish, nutrient-rich conditions [78]. Nitrospira, which was found to be more abundant at sites far away from the pollution source (D2, D3, J2, and J3), has often been found in freshwater ecosystems [79,80], sewage treatment systems [81], and anoxic environments as nitrite oxidizers [82]. Based on the results of RDA (Figure 9a), Nitrospira was positively correlated with NH 4 + -N, NO 3 Cl − -N, TOC, and TSI, but negatively correlated with RI.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that complete nitrification can also occur at low DO levels (Ͻ0.5 mg/liter) (35) or with intermittent aeration (30). Also, a recent theoretical study modeling the risk of failure in nitrification based on the overall oxygen transfer coefficient (K L a) suggested that the risk of failure increases at intermediate aeration rates, while high (K L a Ͼ 35 day Ϫ1 ) and relatively low (4 day Ϫ1 Ͻ K L a Ͻ 10 day Ϫ1 ) aeration rates promote process stability (33).…”
mentioning
confidence: 99%
“…These studies are promising, for though it may take many years to renew the physical assets of the water industry to meet the challenge of a lowenergy and low-carbon footprint, in principle, the less efficient biological assets could be replaced in a few weeks. Studies investigating the type of AOB in both activated sludge flocs and biofilms, where low oxygen was available, have been performed already using culture-independent techniques (12,25,30,34,35), but the results are sometimes conflicting. For example, Park and Noguera (34,35) reported that AOB communities in activated sludge were dominated by members of the Nitrosomonas europaea lineage and the Nitrosomonas oligotropha lineage under low-DO conditions (Ͻ0.24 mg/liter), while members of the N. oligotropha lineage were dominant at higher DO concentrations.…”
mentioning
confidence: 99%
“…Moreover, the AC process is a low-cost solution because it only requires an automatic control system. Nevertheless, because both autotrophic (nitrifying) and heterotrophic (denitrifying) microorganisms will grow in one reactor, many authors (among others Lim et al [12] and Mota et al [13]) noted that an incorrect aeration/non aeration ratio could promote an unbalanced growth of heterotrophic and autotrophic bacteria and worsen the removal efficiencies. Referring in particular to nitrogen removal, previous studies revealed a partial nitrification to nitrite under limiting oxygen condition [14,15].…”
Section: Introductionmentioning
confidence: 99%